Analisis Faktor Yang Mempengaruhi Kepatuhan Protokol Pencegahan Covid-19 Pada Penyandang Diabetes Mellitus - Santi Damayanti (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
ABSTRACT Diabetes Mellitus (DM) is a serious or chronic disease in the long term that describes metabolic disorders or high levels of glucose in the blood because their bodies cannot get enough insulin all the time, the high mortality rate of Covid-19 in people with DM, and the level of compliance with health protocols. less that can trigger the transmission of Covid-19 in people with DM. The purpose of this study was to determine the analysis of factors that affect the compliance of the Covid-19 prevention protocol in people with DM at the Depok 2 Health Center, Sleman Yogyakarta. Using quantitative research methods with a cross sectional approach. The sample in this study were people with DM. The sampling technique used was consecutive sampling. The sample used is 137 respondents. The research instrument used was a questionnaire. Data analysis using Chi Square test. Most of the respondents' knowledge is in the good knowledge category, as much as 80.3%. Most of the respondents' attitudes were in the category of positive attitudes, as many as 81.8%. Education Level Most of them are in the category of high education level, which is 62.0%. Bivariate test results in knowledge of p value = 0.229. Attitude results obtained p value = 0.366, gender p value = 0.021, age p value = 0.613, education level p value = 0.000. At Knowledge, Attitude and age there is no relationship with adherence to the Covid-19 prevention protocol and at the Education Level and gender there is a relationship with Covid-19 prevention compliance. Keywords: Diabetes Mellitus, Covid-19 Prevention Protocol, compliance.